Management Evaluation of Expired and Slow-Moving Medications at Hospital X in Batam City - Putri Meisa Anggesta; Heldi Candra; Oktaviani, Fifin (HM Publisher, 2024)
Efficient drug management necessitates a well-structured supply chain to ensure the smooth functioning of health services. The objective of this study is to ascertain the strategies employed for the disposal of expired medications and the handling of slow-moving pharmaceuticals at Hospital X in Batam City. This research is characterized as descriptive-observational, employing a retrospective methodology. Data analysis involves doing qualitative analysis to assess the degree of rationality, followed by quantitative analysis using a formula. The findings of this study indicate that the highest proportion of expired pharmaceuticals occurred in September 2021, accounting for 25.011%. Additionally, the Regional Public Service Agency (RPSA) allocated 17.020% of the budget expenditures, while the Regional Budget (RB) allocated 28.904%. The pharmaceuticals that have the highest expiration rate are injectable preparations, with a proportion of 63.340%. Among these, 41.299% are funded by RPSA, and 74.075% are funded by RB. The highest proportion of expired pharmaceuticals, categorized by therapeutic class, is 16.500% in the antibiotic group. In addition, RPSA allocates 6.729% of the budget funds and RB allocates 37.123% of the budget for this purpose. The highest proportion of expired pharmaceuticals, categorized by therapeutic class, is 16.500% in the antibiotic group. In addition, RPSA allocates 6.729% of its budget funds and RB allocates 37.123% of its budget towards these expired drugs. In the first quarter, there were 57 slow-moving medications, accounting for 84.594% of the budget money from RPSA and 15.406% from RB. The findings of this study indicate that the management of expired pharmaceuticals does not meet the research criterion of less than 1%; however, the management of slow-moving drugs aligns with the research criterion of less than 1%.